Faktor yang Mempengaruhi Pengungkapan Materialitas pada Laporan Keberlanjutan - Putri, Ira Hutami; Meutia, Inten; Yuniarti, Emylia (E-Jurnal Akuntansi, 2022)
The concept of materiality is now becoming increasingly important for the measurement and reporting of corporate sustainability performance because it can be used as a tool in disclosing material aspects so that sustainability reports are more relevant to stakeholders. This study aims to provide empirical evidence and analyze the effect of financial performance, leverage and firm size on disclosure of materiality in sustainability reports. The research population is a publicly listed company on the Indonesia Stock Exchange for the period 2018 to 2021. The sampling technique uses the purposive sampling method and the final sample is 47 companies. Analysis of the data used is Panel Data Regression. The results of the analysis show that financial performance, leverage and firm size have a positive effect on the disclosure of materiality in the sustainability report. Keywords: Sustainability Report; Financial Performance; Leverage; Firm Size.